Recombinant KRAS G12D Protein Vaccines Elicit Significant Anti-Tumor Effects in Mouse CT26 Tumor Models - Wan, Yuhua; Zhang, Yan; Wang, Gengchong; Mwangi, Patrick Malonza; Cai, Huaman; Li, Rongxiu (Frontiers in Oncology, 2020)
Drug development targeting the most frequently mutation G12D of KRAS has great significance. As an attractive immunotherapy, cancer vaccines can overcome binding difficulties of small molecules; however, the weak immunogenicity and production difficulties of reported KRAS mutation vaccines limit their clinical application. To improve antigen-specific immune responses and anti-tumor ef-fects on tumors expressing KRAS G12D mutation, we designed recombinant proteins of KRAS (amino acids 5-21) with G12D (called SP) in two forms: DTT-SP4 and DTSP. DTT-SP4 was con-structed by fusing four copies of SP to the C-terminal of the translocation domain of diphtheria toxin (DTT), and DTSP was constructed by grafting SP onto DTT. The two vaccines in combination with aluminum hydroxide (Alum) and cytosine preceding guanosine (CpG) successfully induced con-spicuous SP-specific humoral and cellular immune responses, and displayed prominent protective and therapeutic anti-tumor effects in mouse CT26 tumor models. Surprisingly, the DTSP-treated group displayed better anti-tumor effects in vivo compared with the DTT-SP4-treated and control groups. Moreover, 87.5% and 50% of DTSP-treated mice in the preventive and therapeutic models were tumor-free, respectively. Notably, in the DTSP-treated group, the interferon-γ (IFN-γ) expres-sion of T cells in vitro and the T-helper 1 (Th1)-related cytokine expression in tumor tissues indicat-ed that the activated Th1 immune response may be involved in anti-tumor activity. Furthermore, DTSP treatment remarkably altered the subpopulation of T cells in splenocytes and tumor-infiltrating lymphocytes (TILs). The percentage of effector CD8+ T cells increased, whereas that of immunosuppressive CD4+Foxp3+ T cells remained reduced in the DTSP group. Dramatic tumor-inhibitory effects of DTSP, which is easily prepared, make it a more attractive strategy against KRAS G12D tumors.